Analysis of OHS Costs in the Road Construction Project of Singaraja City – Mengwi (Short Cut Bedugul Point 5 - 6) - I Ketut Sutapa; I Nyoman Sutapa; I Wayan Darya Suparta; I Nyoman Ramia; Denin Lintang Tuhujati (Logic : Jurnal Rancang Bangun dan Teknologi, 2021)
Short Cut Bedugul is a short road construction project on the Singaraja-Denpasar route. The short cut development includes the implementation of an occupational health and safety management system (SMK3). The 5-6 point short cut project includes the grade of a large project and places great importance on work safety. Field conditions with high rainfall make the area prone to landslides that can endanger workers, as well as environmental temperatures that reach 20oC which can affect work productivity. The objectives of this study are: To analyze the implementation of occupational safety and health (K3) on the Short Cut project point 5-6 Bedugul. To find out the amount of costs incurred in implementing K3 on the Short Cut point 5-6 Bedugul project. To analyze the percentage of safety and health costs (K3) to the short cut project value point 5-6 Bedugul. The type of research used in this research is descriptive research. and a quantitative descriptive of the construction of the Singaraja City Boundary Road - Mengwi (Short Cut Bedugul point 5–6) the use of K3 such as the use of safety helmets, light vests, masks, gloves, and safety belts is in accordance with the law and is very disciplined and obedient to existing regulations. set. The percentage of K3 costs to the project value refers to the CIRCULAR OF THE MINISTER NO. 66 / SE / M / 2015 Regarding the Cost of Implementing an Occupational Safety and Health Management System (SMK3) Construction in the Public Works Sector is 0.7%.